Virulence of Entomopathogenic Fungus Beauveria Bassiana Isolates to Crocidolomia Pavonana F (Lepidoptera: Crambidae) - Trizelia .; Firdos Nurdin (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2010)
The purpose of this research was to identify the virulent isolates of Beauveria bassiana (Bals.) Vuill. to larvae of Crocidolomia pavonana (F.) and also to investigate the effects of conidial concentrations on larval mortality of C. pavonana. This experiment was conducted at Laboratory of Biological Control, Plant pest and diseases Department, Faculty of Agriculture, Andalas University from April to October 2008. B. bassiana were collected from insects and soils then cultured using selective medium. Thirteen isolates and four different concentration conidia(106-109 conidia/ml) were tested in the experiment. Larvae directly inoculated with conidial suspensions of entomopathogenic fungus. The results showed at a concentration of 108 conidia/ml, isolate HhTK9 was the most virulent caused 82.50% mortality of 2nd instar larvae, with LT50 3.39 days. The mortality C. pavonana larvae was positively correlated with by fungal isolate and conidial concentration.Keywords: Entomopathogenic, Beauveria bas-siana, virulence, isolates, Croci-dolomia pavonana